KESENIAN KEBO BULE (Media Penyiaran Agama Islam di Ponorogo) - Rudianto Rudianto; Bambang Widiyahseno; Ida Widaningrum (MUADDIB Jurnal Kependidikan dan Keislaman, 2020)
This study aims to analyze the art of kebo bule as broadcasting Islam in Sukosari Village, Ponorogo Regency. Data collection techniques used were in-depth interviews, observation, collection and documentation. The research subjects were the heads of the Caucasian arts community, religious leaders and the community. The objects of this study are experiments, concepts, places and activities. steps and data analysis using the Spradley (2016) model are (1) domain analysis, which is to get a general picture of the attractions visited. Look for some observations with grandtour and minitrour; (2) Taxonomic analysis, which is choosing the appropriate domain to be described in more detail, to know the internal structure, and is done with focused observation. (3) Componential analysis finds specific features in each structure by contrasting the elements carried out by interviews and selected observations, and (4) analysis of cultural themes, namely finding relationships between domains that are used together to use themes or titles. The results showed, (1) the art of kebo bule in Ponorogo has historical roots in the emotional connection between Ponorogo and the Keraton Surakarta; (2) the art of kebo bule is a way to preserve local culture of Ponorogo which has historical value; (3) Islamic da'wah media through the art of kebo bule carried out through the performance of the designation, the content of the songs accompanying the arts, Islamic tausiyah, and (4) collaboration of art that combines Javanese art, Reog art, Middle Eastern art, Chinese art, and Balinese art.